Reaktualisasi Persyaratan Perempuan Menjadi Saksi Perkara Perdata Dalam Fikih Klasik Dan Korelasinya Pada Hukum Modern - Akhmad Wafi; Almejiem Aditya Wijaya; Muhammad Noor Ridani; Budi Rahmat Hakim; Muhammad Haris (Fakultas Syariah UIN Antasari, 2023)
Abstract: Testimony between men and women in muamalah (civil) cases in Islamic courts is explicitly verbis mentioned in Surah Al-Baqarah verse 282. But in the contemporary era whether the concept of testimony in the view of the law can be reactualized so as to cause two different points of view. This article proposes a reactualization of a new understanding of how the concept of male and female testimony in the contemporary era is in accordance with the times through an in-depth review by looking at two aspects, namely the influence of modernization on legal novelty and how it is viewed through an Islamic perspective. This research aims to gain a better understanding of the progressivity of Islamic law in line with the times. The research method used is normative law, including analysis of the arguments contained in the Qur'an and relevant Hadith and added some thoughts and literature from scholars. Based on this, the results show that the approach of modernization that affects legal novelty explains that Islamic law always has suitability in any time and place and the reactualization of understanding of the concept of gender in witnesses in Islamic courts can be adjusted by paying attention to legal facts in the trial. Keywords: Contemporary Law; Islamic Court; Witnesses; Women Witnesses